A personalized approach to application of robotic mechanotherapy methods in children with cerebral palsy of different age groups (review) - Ulviia Sh. Ashraphova; Olga S. Kupriianova; Elena K. Karmazina; Olga A. Klochkova; Aiaz M. Mamedieiarov; Elena V. Komarova; Marika I. Ivardava; George A. Karkashadze (Union of pediatricians of Russia, 2023)
Rehabilitation of children with motor disorders is a continuous, staged and dynamic process carried out on the basis of individualization of the program, the effectiveness of which depends on many important factors, starting from the consciousness and motivation of the patient, his rehabilitation potential and ending with the methods of medical rehabilitation used. In recent years, global changes have been taking place in rehabilitation related to the introduction of robotic technology. One of the modern methods is robotic mechanotherapy, with the advantages of the wide possibilities of changing training parameters, continuous computer analysis of motor functions, the possibility of training with simulated movements close to physiological ones. The modern introduction of the possibilities and limitations of the use of robotic complexes in the rehabilitation of children with cerebral palsy will eliminate errors and complications during complex medical rehabilitation and optimally use all the advantages of this method.